Pengaruh Komitmen Organisasi terhadap Kinerja dengan Motivasi dan Kepuasan Kerja sebagai Variabel Pemediasi - Karsono Karsono (Jurnal Akuntansi dan Bisnis, 2008)
The purpose of research: 1) To know commitment organizational influence to motivation; 2) To know influence commitment organizational and motivation to work satisfaction; 3) To know influence commitment organizational motivation and work satisfaction to performance. Data was obtained 175 workers manufacturing industry in Karanganyar Surakarta. The data was analyzed by Structural Equation Modelling (SEM). The result are: 1) commitment organizational is positive significantly influence to motivation; 2) commitment organizational and motivation is positive significantly influence to work satisfaction; 3) commitment organizational, motivation and work satisfaction is positive significantly influence to performance.